IMPLEMENTASI PROGRAM KAMPUNG TEMATIK HOME INDUSTRY DI KELURAHAN KARANGANYAR GUNUNG KECAMATAN CANDISARI KOTA SEMARANG - Wulandari, Destrinanda; Hanani, Retna; Zarkasyi Rahman, Amni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The thematic village program is a program to address community problems in Kota Semarang. Thematic villages are implemented based on unique characteristics that each thematic village has. One of the thematic villages that needs to be researched is the home industry in Karanganyar Gunung Village, Candisari District, Semarang City. The aim of this research is to determine the implementation of the home industry thematic village program and to identify the driving factors and inhibiting factors in the implementation of the home industry thematic village program. Researcher used descriptive qualitative research methods using interview, observation and documentation techniques. The research results show that the home industry thematic village program process is being implemented based on the Mayor's Regulations regarding Guidelines for Implementing Thematic Villages. Starting with the stages of planning procedures, including financing to monitoring and evaluation (monev) which are carried out in accordance with established guidelines. However, its implementation has not yet optimal. This can be seen through the socialization and implementation process which still face several obstacles. Recommendations that can be given are that government needs to be more in-depth in providing information to MSME administrators and actors, the Chair of RW conducts more regular meetings, so that MSME actors increase their self-awareness of technology.